Expected Value 5

Calculus Level 5

Let X n X_n be the minimum of n n numbers chosen randomly and uniformly on the interval [ 1 , 1 ] [-1,1] . Let E n E_n be the expected value of X n 2 {X_n}^2 .

n = 2 ( 1 + E n 1 n ) = 3 4 π cos ( π a 2 ) , \displaystyle\prod _{n=2}^{\infty } \left(1 + \frac{E_n - 1}{n} \right) = \frac{3}{4 \pi} \cos \Bigg(\frac{\pi \sqrt{a}}{2} \Bigg),

where a a is a positive integer. Submit a a .


The answer is 17.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Hasan Kassim
Apr 26, 2018

This approach may be long, but I usually like to use it in solving continuous probability problems.

Divide our interval [ 1 , 1 ] [-1,1] into m m sub-intervals ( m m is very large) each of width 2 m \frac{2}{m} and to be considered as a single value 1 + 2 a m -1+2\frac{a}{m} , where a a can take the values { 1 , 2 , . . . , m } \{1,2,...,m\} .

Now , let { A i } 1 n \{A_{i}\}_{1}^n be n n numbers randomly(and independently) chosen from the given interval, and X X be the random variable corresponding to the minimum chosen number.

Therefore:

A i = 1 + 2 a i m where each variable a 1 , a 2 , . . . , a n is randomly chosen from { 1 , 2 , . . . , m } \displaystyle A_{i} = -1+2\frac{a_{i}}{m} \;\;\;\;\;\;\;\;\; \text{ where each variable } \;\;\; a_1,a_2,...,a_n\;\;\; \text{ is randomly chosen from } \;\;\; \{1,2,...,m\}

and

X can take values of 1 + 2 k m ; k { 1 , 2 , . . . , m } \displaystyle X \;\;\;\text{can take values of}\;\;\; -1+2\frac{k}{m} \;\;;\;\; k\in\{1,2,...,m\}

Note that for every integer 1 j m 1\leq j \leq m :

A j is minimum among { A i } 1 n < = > a j is minimum among { a i } 1 n \displaystyle A_j \;\; \text{is minimum among }\;\{A_i\}_1^n\;\;\;\;\;<=> \;\;\;\;\; a_j \;\;\text{is minimum among }\;\;\{a_i\}_1^n

Therefore we have:

P ( X = 1 + 2 k m ) \displaystyle P\big(X=-1+2\frac{k}{m}\big)

= P ( a 1 = k & a i k i ) + P ( a 2 = k & a i k i ) + . . . + P ( a n = k & a i k i ) ( n 1 ) P ( a i = k i ) \displaystyle =P(a_1=k\;\;\;\&\;\;\; a_i\geq k\;\;\forall i) +P(a_2=k \;\;\;\&\;\;\; a_i\geq k\;\;\forall i)+...+P(a_n=k \;\;\;\&\;\;\; a_i\geq k\;\;\forall i)-\color{#D61F06}{(n-1)P(a_i=k\;\;\forall i)}

(Obviously,the non-red terms are equal)

= n P ( a 1 = k & a i k i ) ( n 1 ) P ( a i = k i ) \displaystyle = nP(a_1=k\;\;\;\&\;\;\; a_i\geq k\;\;\forall i) -\color{#D61F06}{(n-1)P(a_i=k\;\;\forall i)}

And since the a i a_i 's are independent,and that a 1 = k & a 1 k < = > a 1 = k \boxed{a_1=k\;\;\;\&\;\;\; a_1\geq k\;\;<=>\;\;a_1=k\;} :

= n P ( a 1 = k ) P ( a 2 k ) P ( a 3 k ) . . . P ( a n k ) ( n 1 ) P ( a 1 = k ) P ( a 2 = k ) P ( a 3 = k ) . . . P ( a n = k ) \displaystyle =nP(a_1=k)P(a_2\geq k)P(a_3\geq k)...P(a_n\geq k)-\color{#D61F06}{(n-1)P(a_1=k)P(a_2=k)P(a_3=k)...P(a_n=k)}

= n . 1 m . m k + 1 m . m k + 1 m . . . m k + 1 m ( n 1 ) 1 m . 1 m . 1 m . . . 1 m \displaystyle =n.\frac{1}{m}.\frac{m-k+1}{m}.\frac{m-k+1}{m}...\frac{m-k+1}{m}-\color{#D61F06}{(n-1)\frac{1}{m}.\frac{1}{m}.\frac{1}{m}...\frac{1}{m}}

= n m ( m k + 1 m ) n 1 n 1 m n \displaystyle =\frac{n}{m} \bigg(\frac{m-k+1}{m}\bigg)^{n-1}-\frac{n-1}{m^n}

Hence:

E ( X 2 ) = k = 1 m ( 1 + 2 k m ) 2 ( n m ( m k + 1 m ) n 1 n 1 m n ) \displaystyle E(X^2)=\sum_{k=1}^{m} \big(-1+2\frac{k}{m}\big)^2\Bigg(\frac{n}{m} \bigg(\frac{m-k+1}{m}\bigg)^{n-1}-\frac{n-1}{m^n}\Bigg)

= n . 1 m k = 1 m ( 1 + 2 k m ) 2 ( ( m + 1 m k m ) n 1 n 1 m n ) \displaystyle = n.\frac{1}{m}\sum_{k=1}^{m} \big(-1+2\frac{k}{m}\big)^2\Bigg(\bigg(\frac{m+1}{m}-\frac{k}{m}\bigg)^{n-1}-\frac{n-1}{m^n}\Bigg)

Therefore:

E n = lim m E ( X 2 ) = n 0 1 ( 1 + 2 x ) 2 ( ( 1 x ) n 1 0 ) d x \displaystyle E_n=\lim_{m\to \infty} E(X^2)=n\int_0^1 (-1+2x)^2\big((1-x)^{n-1}-0\big)dx

The integral is easy to solve, just use the substitution u = 1 x u=1-x ,then expand and integrate to obtain at last:

E n = n 2 n + 2 n 2 + 3 n + 2 \displaystyle \boxed{E_n=\frac{n^2-n+2}{n^2+3n+2}}

Now, substituting the result in the desired expression to be calculated, we obtain:

P = n = 1 n 2 + 3 n 2 n 2 + 3 n + 2 \displaystyle P=\prod_{n=1}^{\infty} \frac{n^2+3n-2}{n^2+3n+2}

= n = 1 ( n a ) ( n + 3 + a ) ( n + 1 ) ( n + 2 ) \displaystyle =\prod_{n=1}^{\infty} \frac{(n-a)(n+3+a)}{(n+1)(n+2)}

( a a is a root of the upper polynomial,so is 3 a \;-3-a\; since their sum is 3 -3 .)

= n = 1 ( n a ) n = 1 ( n + 3 + a ) n = 1 ( n + 1 ) n = 1 ( n + 2 ) \displaystyle =\frac{\prod_{n=1}^{\infty} (n-a)\color{#20A900}{\prod_{n=1}^{\infty} (n+3+a)}}{\color{#D61F06}{\prod_{n=1}^{\infty} (n+1)}\color{#3D99F6}{\prod_{n=1}^{\infty} (n+2)}}

= n = 1 ( n a ) 1 1 + a 1 2 + a 1 3 + a n = 1 ( n + a ) 1 1 n = 1 ( n ) 1 1 1 2 n = 1 ( n ) \displaystyle =\frac{\prod_{n=1}^{\infty} (n-a)\color{#20A900}{\frac{1}{1+a}\frac{1}{2+a}\frac{1}{3+a}\prod_{n=1}^{\infty} (n+a)}}{\color{#D61F06}{\frac{1}{1}\prod_{n=1}^{\infty} (n)}\color{#3D99F6}{\frac{1}{1}\frac{1}{2}\prod_{n=1}^{\infty} (n)}}

= 2 ( a + 1 ) ( a + 2 ) ( a + 3 ) n = 1 ( 1 a 2 n 2 ) \displaystyle =\frac{2}{(a+1)(a+2)(a+3)}\prod_{n=1}^{\infty}\big(1-\frac{a^2}{n^2}\big)

Now , the above infinite product alone is equal to sin ( π a ) π a \;\frac{\sin (\pi a)}{\pi a}\; ,which is a well known formula and can also be derived easily using the Gamma Function and its Reflection Formula. The value of a a here is any root of the polynomial n 2 + 3 n 2 \;n^2+3n-2\; . So after applying simple trigonometry and some manipulations, we get the desired answer:

3 4 π cos ( π 17 2 ) \displaystyle \boxed{\frac{3}{4\pi}\cos\big(\frac{\pi \sqrt{17}}{2}\big)}

Hints:

E n = n 2 n + 2 n 2 + 3 n + 2 = 1 4 n n 2 + 3 n + 2 E_n = \frac{n^2-n+2}{n^2+3 n+2}=1-\frac{4 n}{n^2+3 n+2} (prove this)

Use sin/cos infinite product formulas to compute:

n = 2 ( 1 4 n 2 + 3 n + 2 ) \displaystyle\prod _ {n = 2}^{\infty}\left (1 - \frac {4} {n^2 + 3 n + 2} \right)

Edit

Here's how to find E n E_n . It's pretty simple. First note that E n E_n is also equal to the expected value of Y 2 Y^2 , where Y is the random variable of the largest of the n numbers (since [ 1 , 1 ] [-1,1] is symmetric about the origin).

Suppose the interval is [ 0 , 1 ] [0,1] not [ 1 , 1 ] [-1,1] . Note that the probability of n-1 of the numbers to be less than x is x n 1 x^{n-1} . Hence translating and dilating to the interval [ 1 , 1 ] [-1,1] , the cdf of Y is ( x / 2 + 1 / 2 ) n 1 (x/2+1/2)^{n-1} . So

E n = 1 1 x 2 ( x 2 + 1 2 ) n 1 d x 1 1 ( x 2 + 1 2 ) n 1 d x E_n = \frac{\displaystyle\int_{-1}^1 x^2 \left(\frac{x}{2}+\frac{1}{2}\right)^{n-1} \, dx}{\displaystyle\int_{-1}^1 \left(\frac{x}{2}+\frac{1}{2}\right)^{n-1} \, dx}

(We have to normalize.)

Anybody else have another way to do it?

Please explain how did you arrive at En ?

Ritik Saxena - 3 years, 6 months ago

Log in to reply

@Ritik Saxena - I edited the solution to show how, hope that helps

Christopher Criscitiello - 3 years, 6 months ago

Don't you need to find n = 2 ( 1 n 4 n 2 + 3 n + 2 ) \prod_{n = 2}^\infty \left ( \frac{1}{n} - \frac{4}{n^2 + 3n + 2} \right ) ?

Alan Yan - 3 years, 6 months ago

Log in to reply

@Alan Yan - Yep, you are right, I made a mistake ... changed the problem to reflect the correct answer ... sorry about that ... thanks!!

Christopher Criscitiello - 3 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...